The Logan Notebooks : Poems - Lindenberg, Rebecca (Mountain west poetry series, 2014)
"Clouds, mountains, flowering trees. Difficult things. Things lost by being photographed. Things that have lost their power. Things found in a rural grocery store. These are some of the lists, poems, prose poems, and lyric anecdotes compiled in The Logan Notebooks, a remix and a reimagining of The Pillow Book of Sei Shonagon, a collection of intimate and imaginative observations about place-a real place, an interior landscape-and identity, at the intersection of the human with the world, and the language we have (and do not yet have) for perceiving it"--